Conflicting Obligations: Considering the Downstream Effects of Human Subjects Research Protections - Reed, Amy R (Rhetoric of health & medicine, 2020)
This article considers the problem of conflicting researcher obligations in RHM, particularly when professional medical rhetoric is analyzed with the goal of improving patient care. Taking one case as illustrative, this article argues that medical professional participants are in positions of relative power, and that their choice to participate in RHM research or not can have downstream effects on more vulnerable patients. Furthermore, this case demonstrates that the interests of medical professional participants may diverge from the interests of their patients. As a result, when RHM researchers assume traditional orientations towards medical professional research participants, they may find themselves unable to advocate for more vulnerable patient populations.